Higher CD4+CD40+ T cells (Th40 cells) associate with systemic lupus erythematosus activity - Lihua Zhu; Guangmei Song; Xiaohui Chen; Yue Zhang; Yanjie Cui; Jie Qiao; Xinran Huang; Xueqin Li; Xiaoen Liu; Xiangbo Zeng; Yangqiu Li; Liang Wang; et al. (Scientific Reports, 2023)
Abstract The aim of this study was to investigate the characteristics of CD4+CD40+ T cells (Th40 cells) in Chinese systemic lupus erythematosus (SLE) patients. Flow cytometry was used to identify the percentage of Th40 cells in peripheral blood from 24 SLE patients and 24 healthy individuals and the level of IL-2, IL-4, IL-6, IL-10, IFN-r, and TNF-α in serum (22 cases) from the SLE patients. Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2000) was used to assess the SLE disease active state. The percentage of Th40 cells in T cells from SLE patients (19.37 ± 17.43) (%) was significantly higher than that from healthy individuals (4.52 ± 3.16) (%) (P < 0.001). The percentage of Th40 cells was also positively associated with SLEDAI-2000 (P = 0.001) and negatively associated with complement C3 (P = 0.007). The Th40 cell percentage was different in SLE patients with different organs involved. The Th40 cell percentage in SLE patients with lupus serositis (29.29 ± 22.19) was significantly higher than that in patients without serositis (13.41 ± 10.79; P = 0.040), and the percentage in SLE patients with lupus pneumonia involvement (29.11 ± 11.88) was significantly higher than that in patients without lupus pneumonia (16.80 ± 17.99; P = 0.043). After 4 weeks treatment, the Th40 cell percentage decreased significantly (P = 0.005). However, Th40 cell expression was not related to cytokines (IL-2, IL-4, IL-6, IL-10, IFN-r, and TNF-α; P > 0.05). A significantly higher percentage of Th40 cells was found in SLE patients, and the Th40 cell percentage was associated with SLE activity. Thus, Th40 cells may be used as a predictor for SLE disease activity and severity and therapeutic efficacy.